Gather together : delightful décor & simple recipes for every occasion - Chubey, Robyn (Rock Point, an imprint of The Quarto Group, 2026)
"Take the stress out of entertaining with Gather Together, a unique collection of easy DIY décor projects and simple, delicious recipes"-- Provided by publisher.